Male infertility and the human microbiome - Magill, Resa G.; MacDonald, Susan M. (Frontiers in Reproductive Health, 2023)
The historical belief in urology was that the genitourinary system should be sterile in a normal, healthy, asymptomatic adult. This idea was perpetuated for decades until research revealed a diverse microbiota existing in human anatomical niches that contributed to both human health and disease processes. In recent years, the search for an etiology and modifiable risk factors in infertility has turned to the human microbiome as well. Changes in the human gut microbiome have been associated with changes in systemic sex hormones and spermatogenesis. Certain microbial species are associated with higher levels of oxidative stress, which may contribute to an environment higher in oxidative reactive potential. Studies have demonstrated a link between increased oxidative reactive potential and abnormal semen parameters in infertile men. It has also been hypothesized that antioxidant probiotics may be able to correct an imbalance in the oxidative environment and improve male fertility, with promising results in small studies. Further, the sexual partner's microbiome may play a role as well; studies have demonstrated an overlap in the genitourinary microbiomes in sexually active couples that become more similar after intercourse. While the potential applications of the microbiome to male fertility is exciting, there is a need for larger studies with uniform microbial sequencing procedures to further expand this topic.